Social trading: do signal providers trigger gambling? - Andreas Oehler; Julian Schneider (Review of Managerial Science, 2022)
Social trading—also referred to as copy trading—is an interactive platform-based innovation facilitating visibility and traceability of signal provider trading activities. Based on published portfolio transaction and return track records, platform users can copy one or several signal providers, i.e. delegate their investment decisions, and thereby become signal followers. Allowing signal providers to administer purely virtual portfolios, in combination with a remuneration scheme based on performance fees and high watermarks, creates convex or option-like incentives (Carpenter, J Finance 55:2311–2331, 18 ; Doering and Jonen, SSRN J, 25 ). We argue that the incentive structure imposed by social trading providers, including a very limited monetary downside risk for signal providers, may motivate traders to gamble. In this context, we assess the factors that have an impact on signal provider lottery-like stock transactions (Bali et al., J Financ Econ 99:427–446, 2 ; Kumar, J Finance 64:1889–1933, 49 ). We provide empirical evidence that signal providers tend to increase the traded relative share of lottery-like stocks when being located at an extreme end of the relative performance spectrum. Furthermore, we provide evidence that underperforming signal providers increase their net exposure towards lottery-like stocks, in turn exposing signal followers to a lottery-like return structure—triggering gambling.
Keywords: G11; G23; G40; 650; Lottery-like Stocks; Gambling; Social Trading